Strategi Kelayakan Penyaluran Kredit Pada Usaha Mikro dan Kecil Di Cirebon (Studi Kasus Bank Syariah Mandiri Cabang Cipto Cirebon Tahun 2018-2020) - Rinaldi, Ricky; Hubeis, Musa; Suryahadi, Suryahadi (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2022)
Bank Syariah Mandiri (BSM) Cipto Cirebon Branch is one of the branches of BSM that focuses on microfinancing to micro and small enterprises (UMK) in Cirebon. The research objectives are (1) to analyze the feasibility of micro-financing in micro, small and medium enterprises (MSMEs) with the 5C principle; (2) to identify environmental factors that affect the feasibility of MSME financing; and (3) to Develop a form of micro-financing strategy for MSMEs. Primary data collection was carried out by direct interviews using questionnaires to experts who mastered the problems. Business feasibility analysis with the 5C principal approach. Strategy analysis with Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), Internal-External (IE) and Strengths, Weaknesses, Opportunities and Threats (SWOT matrix) and Quantitative Strategic Planning Matrix (QSPM) to determine strategic priorities. The results of the financing feasibility analysis with the 5C principle show that the BSM Cipto Cirebon Branch has been implemented well, in accordance with the provisions that have been set. The results of the identification of internal strategy factors were obtained which became the main strength of the Cipto Cirebon Branch of BSM, namely a fairly easy requirement in applying for MSME loans. The main weakness is the lack of human capitals understanding of the product. Government support for microfinance is the main opportunity, while the main threat is the Covid-19 pandemic. Determination of the position of the IE matrix strategy, showing the position of BSM Cipto Cirebon Branch is located in cell V (guard and maintain). The appropriate strategy to be applied is market penetration and product development. Based on the SWOT matrix analysis, eight alternative strategies were identified to be considered, then with the QSP matrix, the strategies that should be prioritized for implementation were obtained, namely to innovate products according to the times and the needs of the community.